2022
DOI: 10.3390/cells11091445
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Function as Immunomodulators in the Intestine in C57Bl/6 Male Mice Exposed to Inhaled Diesel Exhaust Particles on a High-Fat Diet

Abstract: Epidemiological studies reveal a correlation between air pollution exposure and gastrointestinal (GI) diseases, yet few studies have investigated the role of inhaled particulate matter on intestinal integrity in conjunction with a high-fat (HF) diet. Additionally, there is currently limited information on probiotics in mitigating air-pollutant responses in the intestines. Thus, we investigated the hypothesis that exposure to inhaled diesel exhaust particles (DEP) and a HF diet can alter intestinal integrity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Owing to the remarkable acid production capability of JS-3 and its role in enriching SCFA-producing bacteria (Bifidobacterium [38], Lachnospiraceae [39], and Clostridia_UCG-014 [40]), we initially measured the content of fecal SCFAs, which are one of the metabolites of gut microbiota. SCFAs play vital physiological roles, regulating the function of intestinal epithelial cells, maintaining the stability of the intestinal environment, and offering therapeutic benefits for conditions like intestinal inflammation [41]. Our findings indicated a substantial reduction in SCFA levels in hyperuricemic quails, which significantly improved following JS-3 treatment, especially affecting propionic acid, butyric acid, isovaleric acid, and isovaleric acid.…”
Section: Discussionmentioning
confidence: 63%
“…Owing to the remarkable acid production capability of JS-3 and its role in enriching SCFA-producing bacteria (Bifidobacterium [38], Lachnospiraceae [39], and Clostridia_UCG-014 [40]), we initially measured the content of fecal SCFAs, which are one of the metabolites of gut microbiota. SCFAs play vital physiological roles, regulating the function of intestinal epithelial cells, maintaining the stability of the intestinal environment, and offering therapeutic benefits for conditions like intestinal inflammation [41]. Our findings indicated a substantial reduction in SCFA levels in hyperuricemic quails, which significantly improved following JS-3 treatment, especially affecting propionic acid, butyric acid, isovaleric acid, and isovaleric acid.…”
Section: Discussionmentioning
confidence: 63%
“…Complex probiotic treatment more significantly upregulated the expression of this gene in all treatments in this trial. In addition to mucoprotein, Claudin-1, and Occludin proteins are the backbones that mainly constitute the tightly linked chains that reduce the uptake of toxins by the organism during pathogenic bacterial infections ( Phillippi et al, 2022 ). Lactobacillus acidophilus has been shown to increase the expression of Occludin protein for resistance to disruption of the intestinal epithelial barrier by Escherichia coli ( Mehdizadeh Gohari et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to improve clinical characteristics such as elasticity, shine, and thickness, it is essential to enhance the cuticle, cortex, and medulla. Previous studies have shown that probiotic consumption in aged male animals increased subcuticular folliculogenesis, resulting in luxuriant fur and improved anti-inflammation [ 68 ]. Additionally, IGF-1 and EGF have been found to jointly stimulate hair shaft elongation, promote the transition of the hair cycle, and enhance cell proliferation in the outer root sheaths and dermal papilla [ 69 ].…”
Section: Discussionmentioning
confidence: 99%